HAMBATAN-HAMBATAN DALAM PENYELESAIAN PERMASALAHAN HAM OLEH PELAKSANA PELAYANAN KOMUNIKASI MASYARAKAT KANWIL MENKUMHAM DKI JAKARTA - Haryo Nugroho; Aji Wibowo (Jurnal Hukum Adigama, 2020)
Yankomas is the government's effort to resolve human rights issues in the community carried out by Yankomas Implementers. It is further known in resolving issues Human Rights Yankomas has obstacles so that there are many cases that have not yet been completed and have been completed by other agencies. The thesis uses the type of normative research, with the nature of explanatory research. The theories used in this thesis are the rule of law, human rights, human rights violations, human rights enforcement, authority. The results of the study contained communications delivered by the communicators in 2017 and 2018 as well as the results of interviews with the head of human rights at the regional office of the Ministry of Law and Human Rights. The discussion in this thesis is about handling cases of alleged human rights violations through Yankomas in 2017-2018. The conclusion of the thesis is that in 2017 and 2018 there were 18 communications. A total of 7 communications were completed by Yankomas Executors, 6 communications were completed by agencies outside the Yankomas Executors, 2 communications were not yet completed by Yankomas Executors due to Yankomas’ authority to solve the problems, and 3 communications were not completed due to external factors and obstacles experienced by Yankomas Executors in dealing with human rights issues due to 2 things namely the juridical and sociological factors. The steps the country can take in overcoming these obstacles Yankomas' Executors endured by giving them authorities such as mediation and arbiteration.